Effect of Stress Ulcers Prophylaxis, Sedative and Statin on Ventilator-Associated Pneumonia: A Retrospective Analysis Based on MIMIC Database - Kong, Xuetao; Wu, Yaozhou; Wen, Bingqin; Meng, Dongmei; Wei, Li; Yu, Pengjiu (Frontiers in Pharmacology, 2022)
Background: The use of mechanical ventilation(MV) can easily lead to ventilator-associated pneumonia (VAP) such as serious complications or even death, especially in ICU patients . Stress ulcers prophylaxis (SUP) and sedatives have been proved to prevent VAP and improve the prognosis of patients. Our aim was to analyze the effects of stress ulcers prophylaxis, sedative and statin on patients with mechanical ventilation. Methods: Totally, 21400 cases who received mechanical ventilation in ICU from the medical information mart for intensive care (MIMIC IV) database were included. The occurrence of ventilator-associated pneumonia and death in mechanical ventilation patients and ventilator-associated pneumonia patients were explored by multivariate logistic regression and Cox regression to analyze. Results: There were 1131 (5.29%) in ventilator-associated pneumonia group and 20269 (94.7%) in non- ventilator-associated pneumonia group and there were 4313(20.6%) in-hospital mortalities altogether. No protective effect of drugs on ventilator-associated pneumonia was found. Taking sucralfate in mechanical ventilation patients reduced the risk of death compared to taking PPI (aHR = 0.16, 95% CI: 0.04, 0.66). The risk of death was 1.71 times higher in mechanical ventilation patients taking midazolam than in propofol (aHR = 1.71, 95% CI: 1.34, 2.18), 2.24 times higher in ventilator-associated pneumonia patients not taking sedatives than in propofol (aHR = 2.24, 95% CI: 1.20, 4.17), and 2.08 times higher in midazolam than in propofol (aHR = 2.08, 95% CI: 1.06, 4.08). Conclusion: In mechanical ventilation patients, we recommend sucralfate and propofol, and call for the development of drugs for the prevention of ventilator-associated pneumonia.